2013
DOI: 10.1016/j.jchromb.2013.02.035
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of tacrolimus and creatinine from a single dried blood spot using liquid chromatography tandem mass spectrometry

Abstract: Long term therapeutic drug monitoring and assessment of renal function are required in renal transplant recipients on immunosuppressant therapy such as tacrolimus. Dry blood spots (DBS) have been used successfully in the clinic for many years and offers a convenient, simple and non-invasive method for repeated blood tests. We developed and performed a preliminary validation of a method for the analysis of tacrolimus and creatinine from a single DBS using liquid chromatography-tandem mass spectrometric (LC–MS/M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 46 publications
4
63
1
Order By: Relevance
“…As reported by Keevil et al, the correlation between venous blood and fingerprick blood of CRT is high [3]. In spite of these reasons, only Koop et al have reported an assay for CRT in DBS and tacrolimus in DBS [4]. The results were comparable to the reported assay in this article, although a different type of paper was used; the measured CRT in DBS was overall higher compared to whole blood.…”
Section: Resultssupporting
confidence: 71%
“…As reported by Keevil et al, the correlation between venous blood and fingerprick blood of CRT is high [3]. In spite of these reasons, only Koop et al have reported an assay for CRT in DBS and tacrolimus in DBS [4]. The results were comparable to the reported assay in this article, although a different type of paper was used; the measured CRT in DBS was overall higher compared to whole blood.…”
Section: Resultssupporting
confidence: 71%
“…The frequency of these visits can be reduced by the use of DBS. Measurement of drug concentrations in DBS is possible in a range of drugs, 135 including CsA, 136-139 mycophenolic acid, 140 and tacrolimus, 139,141,142 drugs which are frequently prescribed in AD treatment. 143 Measurement of creatinine levels in DBS has also been described.…”
Section: Valorisationmentioning
confidence: 99%
“…143 Measurement of creatinine levels in DBS has also been described. 142 Since decrease in kidney function is one of the most common adverse effects in CsA treatment, measurement of creatinine levels in DBS can be very interesting for the follow-up of AD patients treated with CsA. Combining measurement of drug concentrations in DBS…”
Section: Valorisationmentioning
confidence: 99%
“…In comparison with previously described LC-MS/MS assays to quantify tacrolimus in dried bloods spots [29][30][31][32][33][34]36,39,41,42 , the present assay matches or exceeds their performance in terms of lower limit of quantification, extraction recovery, accuracy and precision while avoiding potentially risky concepts such as one-step protein precipitation procedures and ultra-short chromatography times, which usually give acceptable results during the validation based on blood samples from healthy individuals. However, transplant patients are a highly complex group of patients who have diseases that affect the composition of blood and who take multiple medications.…”
Section: Discussionmentioning
confidence: 82%
“…After a simple finger stick the patient collects a blood drop on a special filter paper card and after the blood spot has dried, it can be mailed to a central laboratory for analysis of tacrolimus and any other immunosuppressant that the patient may currently be taking. This has become possible due to the development of highly sensitive and specific LC-MS/MS assays for the quantification of tacrolimus and other immunosuppressants in very small blood volumes such as dried blood spots (typically 20 µl of blood) 25,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] . Another advantage is that minimally invasive, low volume sample collection strategies such as dried blood spots greatly facilitate therapeutic drug monitoring and pharmacokinetic studies in small children 28 .…”
Section: Introductionmentioning
confidence: 99%